MENINGKATKAN HASIL BELAJAR DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBL) PADA SISWA KELAS 5 AL GHONY SD MUHAMMADIYAH 8 SURABAYA - Umar Haiq; Meirza Nanda Faradita; Iswahyuni (PROCEEDING UMSURABAYA, 2024)
The use of PBL techniques aims to improve student learning outcomes in identifying problems that occur in the environment, especially those related to norms and culture. PBL focuses on the student learning process, encouraging rediscovery, reflection, abstraction, formalization, problem solving, communication, and application of concepts. PBL also supports a fun and student-centered learning process. This research was attended by 21 grade 5 students at SD Muhammadiyah 8 Surabaya, and the process was carried out in two cycles using pre-test, post-test and observation sheets as assessment tools. The final results show an increase in learning outcomes after learning using the PBL method.